Black bodies, dueling pandemics, and the hidden rules for white profit in the NBA. Do Black lives really matter? - Brackett, L. T.; Webster, C. (Philosophy, Sport, and the Pandemic, 2022)
In 2020, Black America was hit with dueling pandemics: the health pandemic of COVID-19 and the pandemic of state-sanctioned violence against Black bodies. The latter has been the primary fight for the Black Lives Matter (BLM) movement, and in 2020 it also became the primary social justice issue across the United States. The continuous unjust deaths of Black people ignited an overdue collective racial justice movement in America. When NBA leadership was ready to return to play, after being halted due to COVID-19, multiple issues converged, making it a decision filled with contention. Black player support for racial justice had become more prominent the past few years and thus Black players, who make up most of the league, knew that their decision about returning to play, not once, but twice, would matter. This chapter focuses on the convergence of white NBA leadership, Black NBA players, COVID-19, and BLM in the 2019-2020 season. Utilizing Critical Race Theory (CRT), the authors showcase the following: the historical underpinnings of race in the NBA; the convergence of racial ramifications with COVID-19; the peak of BLM; and the multiple moving parts of capitalism, all of which are variables in the new wave of Black athlete protest.